The prophet’s earliest teaching of dacwah: Qur’anic view on surah al-Muddaththir and surah al-Muzzammil - Abdul Ghafar Haji Don, (Penerbit Universiti Kebangsaan Malaysia, 2003)
The Qur’an is regarded as the most authentic sources for the Muslims. It lays down the best of guidances in all aspects of human life. For the missionary works (dacwah) it is not exceptional. One can found clearly that there are many verses which are related to dacwah. This article, will however concentrated on two of the earliest Surahs of the Qur’an i.e surah al-Muddaththir and surah al-Muzzammil. A careful study of these Surahs would revealed salient features of dacwah’s teaching like proclamation of the message, proclamation of the greatness of God, rules for hygiene, ethical teachings and the establishment of prayer at night and the recitation of the Qur’an. These teachings were practised by the Prophet in his life as a daci and remain applicable to the modern time